PENGARUH TEKNOLOGI INFORMASI, KEAMANAN, KEPERCAYAAN DAN KUALITAS LAYANAN TERHADAP KEPUASAN NASABAH BANK SYARIAH INDONESIA (Studi Pada Nasabah BSI Wilayah Bandar Lampung) (Al-Mashrafiyah (Jurnal Ekonomi, Keuangan dan Perbankan Syariah), 2026)
The primary objective of this study is to empirically examine the influence of Information Technology, Security, Trust, and Service Quality on Customer Satisfaction within Bank Syariah Indonesia (BSI), focusing specifically on the customer demographic in Bandar Lampung. The study seeks to determine both partial and simultaneous effects of these independent variables. The research methodology employs a quantitative approach utilizing Non-Probability Sampling, specifically Purposive Sampling. A total of 30 respondents who are active users of BSI services were selected. Data collection was conducted via structured questionnaires based on a Likert scale. The analytical framework involves Multiple Linear Regression Analysis processed through IBM SPSS software, comprising validity, reliability, classical assumption, and hypothesis testing. The empirical evidence reveals that collectively, Information Technology, Security, Trust, and Service Quality exert a significant and positive impact on Customer Satisfaction. On a partial basis, Security stands out as the sole variable with a significant positive influence. Conversely, Information Technology, Trust, and Service Quality, while demonstrating a positive relationship direction, do not statistically significantly influence satisfaction levels among BSI customers in the Bandar Lampung region. This study offers a nuanced perspective on consumer behavior in regional Islamic banking. It highlights that in the current digital landscape, the assurance of security outweighs standard service features or IT convenience as the primary driver of satisfaction. This reinforces the relevance of Trust in Online Transactions theory within the broader Expectancy Disconfirmation framework.